A constituição da identidade de uma aluna com deficiência visual: um estudo sobre o processo de inclusão escolar - Leal, Daniela (2008)
The inclusive education has been a theme for great discussions in our society and subject for world events in education. The education in the 21st century has passed through several changes: changes in curriculum parameters, in accessibility, in the universalization of access to school, in the affirmation of affordable education to all, recognition of differences and transformation for everybody's learning and development. In the framework of continuous changes, this research aims to search one of the parts involved in the process: the student with visual deficiency and the constitution of his identity facing the process of education inclusion. Due the nature of the subject searched it was chosen the qualitative approach, as a type of research that take into consideration all elements of a situation in its interactions and influences. In this sense, it was chosen the narrative of her life history, looking for capturing the relationship between the person and the others, because it is believed that this type of approach leads to a greater approximation to the researched/analyzed subject. It was observed the life history of one person who was loosing his vision over the time, caused by pigmentar retinoses. Given by the fact she always attended to regular classes, even before bringing about the subject of inclusive education, he participated into projects of inclusive education, as well assisted by several teaches who provided him with real opportunities of inclusion that added to her "fighting" character along her lifetime, allowing her to achieving the conclusion of a lato sensu graduate degree and become a professional well-known by her critical thinking and questioning positioning